Infusing Islamic ethical ideals in nursing practice - Mohamad Ismail, Mohamad Firdaus; Nurumal, Mohd. Said; Md Isa, Muhammad Lokman; Hashi, Abdurezak Abdulahi (Kulliyyah of Science, International Islamic University Malaysia, 2016)
Nurses are at the heart of healing and medical care, whose duties and responsibilities form an essential element of healthcare. Given the fact that the lives of many patients in hospitals depend on nurses’ moral decency and moral responsibility, certainly moral indecency on the part of nurses impedes, and thus risks the life of millions in hospitals and other nursing places. Apart from that, the lack of the spiritual ethical dimension of life puts nurses in a difficult position to make a moral judgement on given moral issues. This paper attempts to clarify the significant of Islamic ethical ideals in nursing practices. The author tries to explain the meaning of Islamic ethics, unveil the origin of Islamic ethics, and its characteristics. In the meantime, the author tries to present Islamic ethics as an alternative by comparing it with conventional ethics. The paper concludes that the moral of Muslim nurses should be developed along with Islamic ethical ideals, and its application in nursing practices should be prioritised.